UPAYA PELESTARIAN RUMAH ADAT KARO MELALUI RUPA RAGAM HIAS DI SUMATRA UTARA: Rumah adat karo - Seriwati Ginting; Heddy Heriyadi; Sri Bina Carolina (Serat Rupa: Journal of Design, 2021)
The Karo traditional house is one of the cultural heritages in North Sumatra Province. The Karo tribe, is one of the largest tribes. Karo Regency is located on a plateau called Tanah Karo, with a cool climate. It has its own language called cakap Karo, and has Karo script. An area of ??2,127.25 square kilometers with a population of 959,000. The Karo tribe comes with simplicity manifested in an attractive and magnificent traditional house. The Karo traditional house is called Siwalauh Jabu (eight families live in it) The process and life of its inhabitants are arranged in a way. Decorative ornaments in traditional Karo houses are called "carvings." Home decoration patterns are made and placed in the house building with the meanings and values ??of beliefs that are regulated from generation to generation. The color application consists of red, green, black and yellow. Karo traditional houses contain high value and visual decorations built by nature and inspired by fauna and flora, among others, "Lipan nangkih" "bunga lawang" or "flower gateway". This study aims to reveal the patterns and colors of the Karo tribe in house buildings. The method used in this research is descriptive analytical method through observation, interviews, literature study and documentation. The techniques used to analyze are data analysis, data reduction, and reports. The results of the research are the results of a study of the Karo traditional house decoration and its conservation efforts